The impact of microplastics on neurodegenerative diseases and underlying molecular mechanisms: A narrative review - Alexander Weiss; Yuchuan Ding (Wolters Kluwer Medknow Publications, 2024)
The widespread production and disposal of plastics have led to an alarming accumulation of microplastics (MPs) in the environment with significant implications for human health. MPs have infiltrated and accumulated in various ecosystems around the world and consequently in human bodies, posing severe health risks, including the onset of, and acceleration of, neurodegenerative diseases. This review article explores the sources and routes of transmission by which MPs enter the central nervous system, including inhalation and direct penetration of the blood-brain barrier, detection strategies such as engineered nanostructures and gold nanoparticles, and the role of glial cells in exacerbating neurodegenerative diseases such as Alzheimer's diseases, Parkinson's diseases, and multiple sclerosis in the presence of MPs. Further, this paper emphasizes a call for action for further investigation and prevention strategies of the impact of MPs including environmental policy changes, advanced detection methods, and potential therapeutic interventions.